TiZr-based high-entropy alloy additive manufacturing and heat treatment method

Through the additive manufacturing and heat treatment method of TiZr-based high-entropy alloy, the problems of single components, small size, coarse grains and serious segregation in traditional methods are solved, and the efficient preparation and excellent mechanical properties of large-size high-entropy alloy parts are achieved.

CN119747679AActive Publication Date: 2025-04-04NORTHEASTERN UNIV CHINA

Patent Information

Application Number
CN202510264760.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-07
Publication Date
2025-04-04
Estimated Expiration
2045-03-07

AI Technical Summary

Technical Problem

Traditional methods for preparing high-entropy alloys have problems such as single components, small size, coarse grains, and serious segregation, which are difficult to meet the material needs of complex conditions such as high temperature and corrosion resistance.

Method used

Using the TiZr-based high-entropy alloy additive manufacturing method, the pre-alloy powder is melted and deposited by a high-energy laser beam, combined with annealing and solid solution heat treatment, high-entropy alloy parts with good strength, plasticity and toughness matching are prepared.

Benefits of technology

The efficient preparation of large-size high-entropy alloy parts is achieved. The yield strength of the printed sample exceeds 900MPa, the elongation of the fracture exceeds 28%, and the impact toughness after heat treatment reaches more than 55J/cm2, and its performance exceeds that of most high-entropy alloys in the same system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119747679A_ABST
    Figure CN119747679A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of metal powder additive manufacturing, and particularly relates to a TiZr-based high-entropy alloy additive manufacturing and heat treatment method. The TiZrNbVAl high-entropy alloy is prepared in an additive manufacturing mode, the interior of the printed alloy is almost free of air holes, cracks and other defects, and the relative density reaches 96% or above; the microstructure is composed of isometric crystals and columnar crystals, the structure at the lap joint is compact, and the phenomena of poor lap joint and the like are avoided. Compared with traditional electric arc melting, the yield strength of the prepared printing-state high-entropy alloy exceeds 900 MPa, the elongation at break exceeds 28%, the impact toughness is greatly improved after solid solution heat treatment and reaches 55 J / cm < 2 > or above, the performance exceeds that of most of existing same-system high-entropy alloys, and the application range of the printing-state high-entropy alloy is greatly widened. And the preparation efficiency is greatly improved through the double-barrel printing mode, and the double-barrel printing mode is a green and efficient production mode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal powder additive manufacturing, and in particular to a TiZr-based high entropy alloy additive manufacturing and heat treatment method. Background Art

[0002] Different from traditional single-principal alloys, high entropy alloys (HEAs) are a brand-new concept, formally proposed by Taiwan scholar Ye Junwei in 2004. Traditional alloys are composed of one main element and multiple secondary elements. There is no specific main element in high entropy alloys. They are composed of five or more elements, and the atomic content of each element is between 5% and 35%. Because of its high configuration entropy, it is called a high entropy alloy. Due to its special composition, high entropy alloys have four unique effects, namely the high entropy effect in thermodynamics, the hysteresis diffusion effect in kinetics, the lattice distortion effect in structure, and the "cocktail" effect in performance. High entropy alloys are widely used and can be used as high-temperature materials, corrosion-resistant materials, hydrogen storage materials, electrocatalytic materials, etc.

[0003] The traditional method of preparing high entropy alloys is mainly vacuum arc melting, but this method can only produce samples with a single composition and small size, and the alloy also has problems such as coarse grains and severe segregation. As a new material preparation method, additive manufacturing uses laser rapid heating to melt the powder, and then rapidly cools it to solidify. The rapid melting-solidification processing method can produce a very high cooling rate (10 3 ~10 6 K / s), which can not only solve the segregation and shrinkage problems of castings, but also refine the grains and improve the mechanical properties. At the same time, by controlling the supply of powder in real time during multi-barrel printing, alloys with different compositions can be prepared, which can greatly improve production efficiency.

[0004] With the development of material science, the service conditions of alloys are becoming more and more demanding, so the requirements for their comprehensive performance are also getting higher and higher. For example, aircraft generators require materials to have sufficient strength at high temperatures, and protective coatings require materials to have sufficient wear resistance and corrosion resistance to prevent surface damage. As a post-processing method, heat treatment usually enables materials to obtain good mechanical properties, thereby further broadening their scope of use. Summary of the invention

[0005] In view of this, the present invention aims to provide a TiZr-based high entropy alloy additive manufacturing and heat treatment method. The method can be used to process large-sized TiZrNbVAl high entropy alloy parts, and the alloy has good strength, plasticity and toughness matching after heat treatment.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a TiZr-based high entropy alloy additive manufacturing and heat treatment method, comprising the following steps: Ti3Zr 1.5 VtV 0.25 The pre-alloyed powder and V powder are dried separately to remove moisture from their surfaces. The two powders are then placed in two powder feeding barrels, driven by carrier gas to move the powders, and mixed evenly in a powder mixer. Finally, a high-energy laser beam is used to melt the mixed powders and deposit them on the substrate surface to obtain printed samples. The surface of the printed samples is polished and annealed and solution heat treated to obtain heat-treated high-entropy alloys. Among them, Ti3Zr 1.5 VtV 0.25 The average particle size of the pre-alloyed powder is 85.2μm, the powder feeding rate is 10.89g / min, the average particle size of the V powder is 55.0μm, and the powder feeding rate is 0~2.58g / min; the printing power is 1200~1800W, the scanning speed is 6~10mm / s, the overlap rate is 30%, the laser spot diameter is 3.85mm, the Z-axis lifting amount is 0.7~1.3mm, the protective gas flow rate is 15L / min, the carrier gas flow rate is 6L / min, and the oxygen content in the printing chamber is less than 50ppm; The Ti3Zr 1.5 VtV 0.25 The atomic ratio of the pre-alloyed powder and the V powder is 1:0~1:2, and the composition of the prepared heat-treated high entropy alloy is Ti: 34.3~44.4at.%, Zr: 17.1~22.2at.%, Nb: 11.4~14.8at.%, V: 14.8~34.3at.%, Al: 2.9~3.8at.%; Furthermore, in the above-mentioned TiZr-based high-entropy alloy additive manufacturing and heat treatment method, the annealing and solution heat treatment are carried out in a high-temperature heat treatment furnace, and the sample needs to be sealed in a vacuum quartz tube before heat treatment; the annealing treatment includes heating the furnace to 550°C at a heating rate of 10°C / min, placing the sample, keeping warm for 5 hours, and air cooling the sample to room temperature; the solution treatment includes heating the furnace to 1000~1200°C at a heating rate of 10°C / min, placing the sample, keeping warm for 30 minutes, and water-cooling quenching.

[0007] Furthermore, in the above-mentioned TiZr-based high-entropy alloy additive manufacturing and heat treatment method, the drying temperature is 80° C. and the time is 120 minutes.

[0008] Furthermore, in the above-mentioned TiZr-based high entropy alloy additive manufacturing and heat treatment method, the material of the substrate is TC4, pure Ti or pure Zr.

[0009] Furthermore, in the above-mentioned TiZr-based high-entropy alloy additive manufacturing and heat treatment method, the printing state of the high-entropy alloy is divided into block and thin-wall, wherein the block printing layer number is 10 layers, and the thin-wall printing layer number is 60 layers.

[0010] Furthermore, in the above-mentioned TiZr-based high entropy alloy additive manufacturing and heat treatment method, the substrate needs to be polished, cleaned and dried in sequence before use.

[0011] Furthermore, in the above-mentioned TiZr-based high-entropy alloy additive manufacturing and heat treatment method, the protective gas is high-purity argon gas, and the carrier gas is high-purity argon gas.

[0012] Furthermore, the above-mentioned TiZr-based high entropy alloy additive manufacturing and heat treatment method has a yield strength of more than 900MPa and a fracture elongation of more than 28% for the printed sample, and the impact toughness of the high entropy alloy after solution treatment and heat treatment reaches 55J / cm 2 above.

[0013] Compared with the prior art, the present invention has the following advantages: 1. The additive manufacturing method of the high entropy alloy of the present invention is simple, and there are almost no defects such as pores and cracks inside the sample. The overlap is dense and there is no poor overlap, and the relative density reaches more than 96%; 2. The high entropy alloy prepared by the present invention has a yield strength of more than 900 MPa in the printed state and an elongation at break of more than 28%. After solution heat treatment, the impact toughness of the high entropy alloy is greatly improved to 55 J / cm 2 The above performance exceeds that of most high entropy alloys of the same system at present; 3. The additive manufacturing method of the present invention not only has high production efficiency, but also can process large-sized parts, which is a green and efficient production method. The material can be used in aerospace, marine engineering, lightweight materials and other fields. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 The high entropy alloy thin-walled object prepared in Example 7; Figure 2 The metallographic structure of the high entropy alloy thin wall prepared in Example 7; Figure 3 This is the grain scanning morphology of the high entropy alloy obtained in Example 2; Figure 4 This is a scanning morphology image of the polished state of the high entropy alloy obtained in Comparative Example 1; Figure 5 This is the heat treatment process diagram of high entropy alloy; Figure 6 The tensile stress-strain curves of high entropy alloy thin wall before and after solid solution; Figure 7 This is the transmission morphology of the sample in Example 8; Figure 8 This is the cross-sectional morphology of the impact fracture of a high-entropy alloy thin wall. DETAILED DESCRIPTION

[0015] The present invention provides a TiZr-based high entropy alloy additive manufacturing and heat treatment method. In the specific implementation, unless otherwise specified, the raw materials used in the following examples are all commercially available products well known in the art. 1.5 VtV 0.25 The high entropy alloy powder is preferably prepared by rotating electrodes, wherein the electrode running speed is preferably 1.4 mm / s, the arc current is preferably 1500 A, and the alloy rod rotation speed is preferably 21000 r / min.

[0016] In order to enable people in the relevant field to better understand the present invention, the additive manufacturing method of the TiZrNbVAl high entropy alloy provided by the present invention is described in detail below in combination with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.

[0017] Example 1

[0018] This embodiment provides a TiZr-based high entropy alloy additive manufacturing and heat treatment method, which adopts the following steps: Step 1, powder processing: vacuum encapsulated Ti3Zr with an average particle size of 85.2 μm 1.5 VtV 0.25 The high entropy alloy powder and the vacuum encapsulated V powder with an average particle size of 55.0 μm were dried in a blast drying oven at 80°C for 120 min. After drying, the powder was taken out and poured into different powder delivery barrels after cooling to room temperature.

[0019] Step 2, substrate processing: The TC4 substrate is polished with sandpaper until the surface is smooth to remove the oxide scale on the surface, and then the stains on the surface of the substrate are cleaned with acetone, and the TC4 substrate is dried and fixed in the printing chamber.

[0020] Step 3, oxygen-free environment treatment: Cover the printing chamber with a transparent sealing cloth, introduce high-purity argon gas into the chamber, and use an oxygen content detector to detect the oxygen concentration in the chamber in real time. When the oxygen content drops below 50ppm and can be stably maintained at this level, the computer software can be used to set the program to control the robot arm to start printing.

[0021] Step 4, material additive manufacturing: Set the following printing parameters through computer software: Ti3Zr 1.5 VtV 0.25The powder feeding rate is 10.89g / min, the V powder feeding rate is 0g / min, the printing power is 1600W, the scanning speed is 8mm / s, the overlap rate is 30%, the laser spot diameter is 3.85mm, the Z-axis lifting amount is 0.90mm, the carrier gas flow rate is 6L / min, the protective gas flow rate is 15L / min, the number of printing layers is 10, and reciprocating scanning is adopted. After the high entropy alloy sample is prepared, the sample is cooled to room temperature in the chamber and then the high-purity argon gas is turned off, and the printed sample is taken out.

[0022] Step 5, post-processing: Use the wire-cut EDM equipment to cut the printed sample 1 mm above the substrate and polish its surface to obtain the printed Ti3Zr 1.5 VtV 0.25 High entropy alloy block, whose composition is Ti: 44.4 at.%, Zr: 22.2 at.%, Nb: 14.8 at.%, V: 14.8 at.%, Al: 3.8 at.%.

[0023] Example 2

[0024] This embodiment is a TiZr-based high entropy alloy additive manufacturing and heat treatment method, which is different from Example 1 in that: the printing power is 1200 W, the scanning speed is 6 mm / s, and the Z-axis lifting amount is 1.30 mm.

[0025] Example 3

[0026] This embodiment is a TiZr-based high entropy alloy additive manufacturing and heat treatment method, which is different from Example 1 in that: the printing power is 1500W, the scanning speed is 10mm / s, and the Z-axis lifting amount is 0.85mm.

[0027] Example 4

[0028] This embodiment is a TiZr-based high entropy alloy additive manufacturing and heat treatment method, which is different from Example 1 in that: the printing power is 1800 W, the scanning speed is 10 mm / s, and the Z-axis lifting amount is 0.85 mm.

[0029] Example 5

[0030] This embodiment is a TiZr-based high entropy alloy additive manufacturing and heat treatment method, which is different from the embodiment 1 in that the V powder feeding rate is 1.29 g / min, the printing power is 1500 W, the scanning speed is 10 mm / s, and the Z axis lifting amount is 1.10 mm. The obtained printed high entropy alloy block Ti3Zr 1.5 NbV2Al 0.25 The composition is Ti: 38.7 at.%, Zr: 19.4 at.%, Nb: 12.9 at.%, V: 25.8 at.%, Al: 3.8 at.%.

[0031] Example 6

[0032] This embodiment is a TiZr-based high entropy alloy additive manufacturing and heat treatment method, which is different from the embodiment 1 in that the V powder feeding rate is 2.58 g / min, the printing power is 1500 W, the scanning speed is 10 mm / s, and the Z axis lifting amount is 1.15 mm. The obtained printed high entropy alloy block Ti3Zr 1.5 NbV3Al 0.25 The composition is Ti: 34.3 at.%, Zr: 17.1 at.%, Nb: 11.4 at.%, V: 34.3 at.%, Al: 2.9 at.%.

[0033] Example 7

[0034] This embodiment is a TiZr-based high-entropy alloy additive manufacturing and heat treatment method, which is different from Example 1 in that: this method prepares thin-walled parts, the Z-axis lift is 0.7 mm, the number of printing layers is 60, and reciprocating scanning is used. In order to compensate for the collapse caused by heat accumulation, the Z-axis lift of the 20th, 30th, 40th, and 50th layers is 0, and after each layer is printed, wait 30 seconds before printing the next layer.

[0035] Example 8

[0036] This embodiment is a TiZr-based high entropy alloy additive manufacturing and heat treatment method, which is different from Example 7 in that the thin wall prepared in Example 7 is annealed and solution heat treated. The printed thin wall is cut off from the substrate by an electric spark wire cutting machine, its surface is polished and a vacuum quartz tube is sealed to prevent the sample from being oxidized during the heat treatment process, and then annealed and solution heat treated in a high-temperature heat treatment furnace. The annealing treatment includes heating the furnace to 550°C at a heating rate of 10°C / min, placing the sample, keeping warm for 5h, and air cooling the sample to room temperature; the solution treatment includes heating the furnace to 1000~1200°C at a heating rate of 10°C / min, placing the sample, keeping warm for 30min, and water-cooling quenching.

[0037] Example 9

[0038] This embodiment is a TiZr-based high entropy alloy additive manufacturing and heat treatment method, which is different from Example 8 in that: the solid solution temperature is 1200° C., the holding time is 30 minutes, and the quenching is water-cooled.

[0039] Comparative Example 1 A TiZr-based high entropy alloy additive manufacturing and heat treatment method, which is different from Example 1 in that: printing power is 600W, scanning speed is 4mm / s, and Z-axis lifting amount is 0.85mm.

[0040] Comparative Example 2 A TiZr-based high entropy alloy additive manufacturing and heat treatment method, which is different from Example 1 in that: printing power is 900 W, scanning speed is 4 mm / s, and Z-axis lifting amount is 0.85 mm.

[0041] Performance Testing The TiZrNbVAl high entropy alloy blocks prepared in Examples 1 to 6 and Comparative Examples 1 to 2 were cut into compression and microstructure characterization samples along the sinking direction. The printed and heat-treated thin walls prepared in Examples 7 to 9 were cut into tensile samples and impact samples along the scanning direction. Microstructure characterization samples were cut along the deposition direction, and a V-shaped notch was opened along the impact sample near the substrate.

[0042] Figure 1 This is the printed high-entropy alloy thin wall prepared in Example 7. It can be seen that the surface of the thin-walled part is smooth and the overlap is good. Figure 2 This is the metallographic structure of the printed thin wall along the deposition direction of Example 7. It can be seen that the equiaxed crystals and columnar crystals in the sample are alternately distributed, which is a typical additive manufacturing structure. Figure 3 This is a high-magnification scanning morphology image of Example 2, showing that the grain size is uniform, with an average grain size of less than 40 μm. The above results show that no obvious defects are found in the printed sample from a macroscopic and microscopic perspective, which indicates that the parameter selection is reasonable. Figure 4 This is the polished scanning morphology of Comparative Example 1. Due to inappropriate parameter selection, holes and unmelted powder appeared in the sample, which had an adverse effect on the mechanical properties and relative density.

[0043] The compressive yield strength and relative density of the TiZrNbVAl high entropy alloy blocks obtained in Examples 1 to 6 and Comparative Examples 1 to 2 are shown in Table 1. 1.5 VtV 0.25 The compressive yield strength of the high entropy alloy shows a high degree of consistency, and its compressive yield strength range is 1061~1092MPa, which shows that the alloy has great compatibility with the additive manufacturing process, and the alloy can obtain excellent mechanical properties within this process range. At the same time, the relative density of the alloy reaches more than 96%, which means that the alloy prepared in this process has few defects and high density. In addition, with the increase of V content, the compressive yield strength of TiZrNbVAl high entropy alloy also increases, which can reach 1480MPa, which shows that the V element can play a certain strengthening effect. The compressive yield strength and relative density of comparative examples 1~2 are lower than those of the embodiment, which shows that the process selection of the comparative example is inappropriate.

[0044] Table 1 Compressive yield strength and relative density of TiZrNbVAl high entropy alloy

[0045] Figure 5 This is a process diagram for annealing and solution heat treatment. Usually, high-temperature solution treatment can reduce element segregation. Figure 6 The engineering stress-strain curves of the samples before and after heat treatment of the high entropy alloy show that the printed samples show excellent strength-plasticity matching, with a yield strength of more than 900MPa and an elongation at break of more than 28%. As the solution temperature increases, the strength remains basically unchanged, but the plasticity decreases to a certain extent. Table 2 shows the mechanical properties of the high entropy alloy before and after heat treatment. Comprehensive analysis shows that the samples heat treated at 1000℃ show the best comprehensive mechanical properties. Compared with the printed state, the strength remains almost unchanged, the elongation at break is reduced by 12.7%, but the impact toughness is increased by 201%, reaching 55J / cm 2 . Figure 7 This is the transmission morphology of the sample after solution heat treatment at 1000℃. It can be seen that the grain boundaries in the matrix are obvious and present a single-phase structure. Figure 8 This is the cross-sectional morphology of the impact sample fracture. The fracture of the printed sample is smooth, while the fracture cross-section of the solution heat treated sample has great fluctuations, which indicates that the solution heat treated sample has undergone great plastic deformation during the fracture process.

[0046] Table 2 Comparison of mechanical properties of high entropy alloys before and after solid solution

[0047] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A TiZr-based high entropy alloy additive manufacturing and heat treatment method, comprising the following steps: Ti3Zr 1.5 VtV 0.25 The pre-alloyed powder and V powder are dried separately to remove moisture from their surfaces. The two powders are then placed in two powder feeding barrels, driven by carrier gas to move the powders, and mixed evenly in a powder mixer. Finally, a high-energy laser beam is used to melt the mixed powders and deposit them on the substrate surface to obtain printed samples. The surface of the printed samples is polished clean, and annealing and solution heat treatment are performed to obtain heat-treated high-entropy alloys. Among them, Ti3Zr 1.5 VtV 0.25 The average particle size of the pre-alloyed powder is 85.2μm, the powder feeding rate is 10.89g / min, the average particle size of the V powder is 55.0μm, and the powder feeding rate is 0~2.58g / min; the printing power is 1200~1800W, the scanning speed is 6~10mm / s, the overlap rate is 30%, the laser spot diameter is 3.85mm, the Z-axis lifting amount is 0.7~1.3mm, the protective gas flow rate is 15L / min, the carrier gas flow rate is 6L / min, and the oxygen content in the printing chamber is less than 50ppm; The Ti3Zr 1.5 VtV 0.25 The atomic ratio of pre-alloyed powder and V powder is 1:0~1:2, and the composition of the prepared heat-treated high entropy alloy is Ti: 34.3~44.4at.%, Zr: 17.1~22.2at.%, Nb: 11.4~14.8at.%, V: 14.8~34.3at.%, Al: 2.9~3.8at.%.

2. The TiZr-based high entropy alloy additive manufacturing and heat treatment method according to claim 1, characterized in that: The annealing and solution heat treatment are carried out in a high-temperature heat treatment furnace, and the sample needs to be sealed in a vacuum quartz tube before the heat treatment; the annealing treatment includes heating the furnace to 550°C at a heating rate of 10°C / min, placing the sample, keeping it warm for 5 hours, and air cooling the sample to room temperature; the solution treatment includes heating the furnace to 1000-1200°C at a heating rate of 10°C / min, placing the sample, keeping it warm for 30 minutes, and water-cooling quenching.

3. The TiZr-based high entropy alloy additive manufacturing and heat treatment method according to claim 1, characterized in that: The drying temperature is 80° C. and the drying time is 120 min.

4. The TiZr-based high entropy alloy additive manufacturing and heat treatment method according to claim 1, characterized in that: The substrate is made of TC4, pure Ti or pure Zr.

5. The TiZr-based high entropy alloy additive manufacturing and heat treatment method according to claim 1, characterized in that: Before using the substrate, it needs to be polished, cleaned and dried in sequence.

6. The TiZr-based high entropy alloy additive manufacturing and heat treatment method according to claim 1, characterized in that: The protective gas is high-purity argon gas, and the carrier gas is high-purity argon gas.

7. The TiZr-based high entropy alloy additive manufacturing and heat treatment method according to claim 1, characterized in that: The yield strength of the printed sample exceeds 900MPa, the elongation at break exceeds 28%, and the impact toughness of the high entropy alloy after solution heat treatment reaches 55J / cm 2 above.

Citation Information

Patent Citations

  • High-specific-gravity energetic double-phase high-entropy alloy and preparation method thereof

    CN115369299A

  • Additive manufacturing method and application of refractory high-entropy alloy

    CN118751933A

  • High-entropy titanium-aluminum alloy and laser melting deposition preparation method thereof

    CN119260020A

  • Additive manufacturing method for WC-reinforced high-entropy alloy-based composite material

    CN119346886A

  • Additively manufactured high-temperature aluminum alloys, and feedstocks for making the same

    EP3902934A2

Cited By

  • High-specific-strength light refractory high-entropy alloy and preparation method and application thereof

    CN122406073A